We know the derivative of e^{x}, which is e^{x}.
(e^{x})' = e^{x}
We can find the derivative of e^{sin√x} using chain rule.
Find ᵈʸ⁄dₓ, if
y = e^{cos√x}
Let u = √x.
y = e^{cos}^{u}
Let v = cosu.
y = e^{v}
Now,
y = e^{v} ----> y is a function of v
v = cosu ----> v is is a function of u
u = √x ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = e^{v}, v = cosu and u = √x.
Substitute v = cosu.
Substitute u = √x.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Jun 24, 24 01:38 AM
Jun 22, 24 10:26 PM
Jun 22, 24 05:38 AM